PAI Teachers' Creativity in Utilizing Digital-Based Learning Media - Reksiana Reksiana; Sayyidah Humaeroh (Jurnal Syntax Transformation, 2023)
The research raises the issue of the rise of teachers who do not have the power of creativity in the era of digitalization of education. This study aims to analyze the development of creativity of PAI teachers at SMK Miftahul Falah Jakarta in utilizing information technology-based learning media. The research method used in this study is a qualitative method with a descriptive approach. The object of this research is SMK Miftahul Falah Jakarta. The primary data sources of this study are 1 PAI teacher, 1 student and 1 student. While secondary data in the form of books, journals and articles, and documentation sources of learning activities in the classroom, learning media used, and school profiles. Data collection techniques are through observation, interview and documentation methods. The data analysis technique uses Miles and Huberman data analysis with three stages, namely data reduction, data presentation, withdrawal. The findings in the study are that the development of digital-based media creativity carried out by PAI teachers at SMK Miftahul Falah Jakarta has an impact on four aspects. First, the aspect of fluency of thinking is seen from the learning steps carried out. Both aspects of flexibility of thinking are seen from the creation of information technology-based learning media and motivation. The three aspects of originality are seen from trainings on the use of information technology-based learning media. The four aspects of elaboration (elaboration) are seen from the creativity of PAI teachers in developing the potential of students through the use of information technology-based learning media. Another finding is that if PAI teachers use ICT-based learning media, it will have an impact on increasing the motivation and enthusiasm of students in learning PAI.